Role of RND Efflux Pumps in Drug Resistance of Cystic Fibrosis Pathogens - Viola Camilla Scoffone; Gabriele Trespidi; Giulia Barbieri; Samuele Irudal; Elena Perrin; Silvia Buroni (Antibiotics, 2021)
Drug resistance represents a great concern among people with cystic fibrosis (CF), due to the recurrent and prolonged antibiotic therapy they should often undergo. Among Multi Drug Resistance (MDR) determinants, Resistance-Nodulation-cell Division (RND) efflux pumps have been reported as the main contributors, due to their ability to extrude a wide variety of molecules out of the bacterial cell. In this review, we summarize the principal RND efflux pump families described in CF pathogens, focusing on the main Gram-negative bacterial species (Pseudomonas aeruginosa, Burkholderia cenocepacia, Achromobacter xylosoxidans, Stenotrophomonas maltophilia) for which a predominant role of RND pumps has been associated to MDR phenotypes.